2022
DOI: 10.1249/jes.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Pathways Underlying Individual Differences in Regular Physical Activity

Abstract: Twin and family studies show a strong contribution of genetic factors to physical activity (PA) assessed by either self-report or accelerometers. PA heritability is around 43% across the lifespan. Genome-wide association studies have implied biological pathways related to exercise ability and enjoyment. A polygenic score based on genetic variants influencing PA could help improve the success of intervention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 129 publications
0
15
0
Order By: Relevance
“…An alternative approach compares the relative importance of shared environmental and genetic influences in monozygotic and dizygotic twin pairs. 12 This provides a platform to determine whether shared environment explains more variation than genetic influences, in which case looking for associations with specific genotypes is extremely difficult. In the current study, rMZ were typically high and rDZ very low, indicating that factors shared between monozygotic twins are important influences on training-induced changes in FMD% and GTN%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An alternative approach compares the relative importance of shared environmental and genetic influences in monozygotic and dizygotic twin pairs. 12 This provides a platform to determine whether shared environment explains more variation than genetic influences, in which case looking for associations with specific genotypes is extremely difficult. In the current study, rMZ were typically high and rDZ very low, indicating that factors shared between monozygotic twins are important influences on training-induced changes in FMD% and GTN%.…”
Section: Discussionmentioning
confidence: 99%
“…35 The latter, genome-wide association, is less impacted by a priori bias but requires hundreds of thousands of participants to identify genetic variants in highly polygenic phenotypes. 12 Indeed, genome-wide association has demonstrated that the contribution of single variants to physiological outcomes is typically very small; 12,36 for example 9 single nucleotide polymorphisms may explain ≈2% of the variance in VO 2 max, while another 7 contribute only 1% to 2%. An alternative approach compares the relative importance of shared environmental and genetic influences in monozygotic and dizygotic twin pairs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations